2022
DOI: 10.1111/ijac.14035
|View full text |Cite
|
Sign up to set email alerts
|

Reactive air brazing of 3YSZ ceramic to aluminized Crofer22H stainless steel using Ag–CuO fillers

Abstract: In this work, an effective protected Al2O3 layer was fabricated first on the surface of Crofer22H by reactive air aluminization to suppress cathodic poisoning in solid oxide fuel cells. Then, the reactive air brazing of aluminized Crofer22H to 3YSZ ceramics was carried out by using Ag–CuO fillers. The effects of CuO content and brazing temperature on the interfacial microstructure and mechanical properties of the joints were studied in detail. The results indicated that maintaining a continuous Al2O3 layer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…When the CuO content was above 4 mol.%, the liquid filler consisted of Ag‐rich liquid phase L2 and CuO‐rich liquid phase L1. The studies in the literature have shown that the CuO‐rich L1 liquid phase showed a stronger affinity for ceramics and tended to enrich at the interface 27,37,38 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the CuO content was above 4 mol.%, the liquid filler consisted of Ag‐rich liquid phase L2 and CuO‐rich liquid phase L1. The studies in the literature have shown that the CuO‐rich L1 liquid phase showed a stronger affinity for ceramics and tended to enrich at the interface 27,37,38 …”
Section: Resultsmentioning
confidence: 99%
“…The studies in the literature have shown that the CuO-rich L1 liquid phase showed a stronger affinity for ceramics and tended to enrich at the interface. 27,37,38 In fact, the L1 liquid phase was not a eutectic liquid phase. The monotectic reaction occurred during natural cooling, as shown in Equation (1) to form the solid phase CuO and L2 liquid phase, which would not show eutectic structure at room temperature.…”
Section: The Quenching Interfacial Microstructure Of Different Filler...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, efforts have been made to limit interdiffusion by using diffusion barriers. For instance, Zhou et al [60] applied an aluminum coating to Crofer22H, while Si et al [62] utilized Mn-Co spinel-coated Crofer22APU as their substrates.…”
Section: Soec/sofcmentioning
confidence: 99%
“…This has minimized the deterioration of the brazed elements to a certain extent; at the same time, the gas tightness has been increased even under substantial pressure differentials. Enhancements have been implemented to address the unacceptable decline in strength and gas tightness during prolonged periods of stationary service as well as during start-stop cycles [8,60,107]. The RAB process has a significant drawback wherein it introduces an excessive amount of oxygen into the brazed joint.…”
Section: Soec/sofcmentioning
confidence: 99%